Towards Sustainable Management of Natural and Built Capital for a Greener, Diversified, and Resilient Economy : Policy Note for Mongolia - World Bank (World Bank, Washington, DC, 2020)
Mongolia is endowed with rich natural resources, including its vast pastureland, unspoiled nature, and world-class mineral deposits. However, despite the strategic opportunities, Mongolia’s economy is characterized by its heavy reliance on mining, unsustainable exploitation of natural resources, poor livestock farming, unplanned urban development, and poor infrastructure connectivity with associated urban congestion and higher cost of infrastructure services. The COVID-19 (Coronavirus) pandemic further exacerbates the challenges that Mongolia faces to achieve its medium- and long-term goals. This policy note identifies four key priority reform areas towards sustainable management of natural and built capital for a greener, diversified, and resilient economy.